The Influence of Brand Marketing Strategy, Price Discounts and Formation of Loyalty on Consumer Repurchase Intentions on the Shopee Platform (Literature Review Management Students at Bhayangkara University, Jakarta Raya - Bekasi) - Teti Aliyanti (Greenation Research & Yayasan Global Resarch National, 2024)
This research aims to analyze the influence of brand marketing strategies and price discounts on the formation of consumer loyalty and repurchase intentions on the Shopee e-commerce platform. In the competitive digital era, understanding the factors that influence consumer loyalty and repeat purchase intentions is crucial for the sustainability of e-commerce businesses. This study uses a quantitative approach with a sample of Management students from Bhayangkara University, Jakarta Raya - Bekasi who are Shopee customers. This research shows that implementing brand marketing strategies and providing price discounts has a significant impact on customer loyalty and intention to make repeat purchases. These findings provide valuable insight for e-commerce business players in designing effective marketing strategies to increase consumer loyalty. and encourage repeat purchases.